Reproductive health education for female sex workers in Bandungan District - Wulandari, Respati; Aprianti, Aprianti; Sifai, Izzatul Alifah; Pramitasari, Ratih (Community Empowerment, 2025)
Female Sex Workers (FSWs) are a group vulnerable to HIV, violence, unwanted pregnancies, and sexually transmitted infections (STIs) due to limited access to information and reproductive health services. This community service aims to improve the knowledge and attitudes of FSWs and shelter managers regarding reproductive health. The activity was conducted using counseling methods, including material presentations, discussions, and experience sharing. The results of the activity showed an increase in the average knowledge score (from 55.7 to 65.7) and attitude score (from 27.9 to 29.6) after the counseling. Although this program successfully improved reproductive health knowledge and attitudes, cross-sectoral collaboration between the Health Office, Community Health Centers (Puskesmas), NGOs, and academics is still needed to optimize programs and reproductive health services for FSWs.